Digital Warehouse System for Vegetable Preservation - Viswanathan, Munusami (Journal of Electronics and Informatics, 2023)
Vegetable preservation is the process of storing vegetables for longer days by treating them in a right way. This enables the vegetables to not get waste from natural process. There are several technics followed in the agriculture field for preservation based on the nature of vegetables and fruits. Drying, pickling, canning, freezing, fermenting, salting and oil packing are some of the techniques that are widely employed for vegetable preservation. The proposed work aims to regulate the vegetable preservation process in the warehouse system by treating them with an automatic strategy. The strategy controls the temperature and humidity of the warehouse through customized fuzzy control algorithm included in the arduino microcontroller. The algorithm is designed to specify the kind of vegetable placed in the warehouse module for estimating the required temperature and humidity by its own. An experimental study is performed in the work to project the betterment of the work in terms of vegetable preserving days and efficiency over the manual and uncontrolled preservation methods.
Keywords: Automated warehouse; preservation methodologies; sensors in agriculture; wastage control; climate control